High mobility In0.75Ga0.25As quantum wells in an InAs phonon lattice. (16th February 2018) - Chen, C; Holmes, S N; Farrer, I; Beere, H E; Ritchie, D A
Abstract: InGaAs based devices are great complements to silicon for CMOS, as they provide an increased carrier saturation velocity, lower operating voltage and reduced power dissipation (International technology roadmap for semiconductors (www.itrs2.net )). In this work we show that In0.75 Ga0.25 As quantum wells with a high mobility, 15 000 to 20 000 cm 2 V −1 s −1 at ambient temperature, show an InAs-like phonon with an energy of 28.8 meV, frequency of 232 cm −1 that dominates the polar-optical mode scattering from ̃70 K to 300 K. The measured optical phonon frequency is insensitive to the carrier density modulated with a surface gate or LED illumination. We model the electron scattering mechanisms as a function of temperature and identify mechanisms that limit the electron mobility in In0.75 Ga0.25 As quantum wells. Background impurity scattering starts to dominate for temperatures <100 K. In the high mobility In0.75 Ga0.25 As quantum well, GaAs-like phonons do not couple to the electron gas unlike the case of In0.53 Ga0.47 As quantum wells.